Early-Stage Melt-Rock Reaction in a Cooling Crystal Mush Beneath a Slow-Spreading Mid-Ocean Ridge (IODP Hole U1473A, Atlantis Bank, Southwest Indian Ridge) - Sanfilippo, Alessio; MacLeod, Christopher J.; Tribuzio, Riccardo; Lissenberg, C. Johan; Zanetti, Alberto (Frontiers in Earth Science, 2020)
Microtextural and chemical evidence from gabbros indicates that melts may react with the crystal framework as they migrate through crystal mushes beneath mid-ocean ridges; however, the importance of this process for the compositional evolution of minerals and melts remains a matter of debate. Here we provide new insights into the extent by which melt-rock reaction process can occur in oceanic gabbros by conducting a detailed study of cryptic reactive melt migration as preserved in an apparently unremarkable, homogeneous olivine gabbro from deep within a section of the plutonic footwall of the Atlantis Bank core complex on the Southwest Indian Ridge (IODP Hole U1473A). High-resolution chemical maps reveal that mineral zoning increases towards and becomes extreme within a cm-wide band that is characterised by elevated incompatible trace element concentrations and generates extreme more/less incompatible element ratios. We demonstrate that neither crystallisation of trapped melt nor diffusion can account for these observations. Instead, taking the novel approach of correcting mineral-melt partition coefficients for both temperature and composition, we show that these chemical variations can be generated by intergranular reactive porous flow of a melt as it migrated through the mush framework, and whose composition evolved by melt-rock reaction as it progressively localised into a cm-scale reactive channel. We propose that the case reported here may represent, in microcosm, a preserved snapshot of a generic mechanism by which melt can percolate through primitive mafic (olivine gabbro) crystal mushes, and be modified towards more evolved compositions via near-pervasive reactive transport.